2010
DOI: 10.1038/ejhg.2010.148
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome trisomies in Europe: prevalence, prenatal detection and outcome of pregnancy

Abstract: This study aims to assess prevalence and pregnancy outcome for sex chromosome trisomies (SCTs) diagnosed prenatally or in the first year of life. Data held by the European Surveillance of Congenital Anomalies (EUROCAT) database on SCT cases delivered 2000-2005 from 19 population-based registries in 11 European countries covering 2.5 million births were analysed. Cases included were livebirths diagnosed to 1 year of age, fetal deaths from 20 weeks gestation and terminations of pregnancy for fetal anomaly (TOPFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 21 publications
1
61
0
1
Order By: Relevance
“…In a recent European study of the EUROCAT working group, 0.054 triple X patients/1000 births were observed. 26 In our EA/TEF cohort, the incidence rate of Chromosome X changes in patients with EA/TEF E Brosens et al triple X syndrome is 1.12%, with an average maternal age of 30.8 years, which is 11 times higher than that in the estimated general population and 6.5 times higher than in the calculated incidence rate by Haverty et al 25 Guichet et al 27 reviewed prenatally and postnatally diagnosed 47,XXX karyotypes from 18 laboratories. Mental retardation or congenital malformations were described in over one-third of the 190 patients reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent European study of the EUROCAT working group, 0.054 triple X patients/1000 births were observed. 26 In our EA/TEF cohort, the incidence rate of Chromosome X changes in patients with EA/TEF E Brosens et al triple X syndrome is 1.12%, with an average maternal age of 30.8 years, which is 11 times higher than that in the estimated general population and 6.5 times higher than in the calculated incidence rate by Haverty et al 25 Guichet et al 27 reviewed prenatally and postnatally diagnosed 47,XXX karyotypes from 18 laboratories. Mental retardation or congenital malformations were described in over one-third of the 190 patients reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 The most common chromosome abnormalities are trisomies 21, 18 and 13, and the sex chromosome abnormalities. 2 Little detailed information is available on rarer chromosome abnormalities diagnosed prenatally or in infancy.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome is found in 1 of 1.000 male births [5,6] even if other studies have reported a different prevalence [4,[7][8][9][10][11][12].…”
Section: Xyy Syndromementioning
confidence: 96%
“…First of all, the analysis of the literature shows that about the 75% of cases of Jacobs' Syndrome are not detected prenatally or postnatally [61], because these subjects often have an adequate mental and psychological development [70,71] and therefore often the diagnosis is accidental, delayed or even absent [5,61].…”
Section: Discussionmentioning
confidence: 99%